Outcomes of Patients With Cirrhosis Undergoing Orthopedic Procedures: An Analysis of the Nationwide Inpatient Sample. Issue 9 (October 2019) - Parikh, Neehar D.; Chang, Yu-Hui; Tapper, Elliot B.; Mathur, Amit K.
Abstract : Introduction: The population of patients with cirrhosis is growing and shifting toward a more elderly demographic and thus are at risk of developing orthopedic complications. There is lack of data on safety of orthopedic procedures in this population. Methods: We performed an analysis of the Nationwide Inpatient Sample from 2005 to 2011 for patients undergoing hip arthroplasty, knee arthroplasty, and spinal laminectomy/fusion, stratified by presence of cirrhosis. The primary endpoint was in-hospital mortality and secondary endpoints included length of stay (LOS) and costs. Results: There were 693, 610 inpatient stays for orthopedic procedures conducted during the study period, with 3014 (0.43%) patients coded as having cirrhosis. Patients with cirrhosis had a lower median age (62 vs. 66 y; P <0.001) and were more likely to be male (52.3% vs. 41.1%; P <0.001). The inpatient mortality rate was significantly higher in patients with cirrhosis (2.4% vs. 0.4%; P <0.001) as was median LOS (4 vs. 3 d; P <0.001) and mean costs ($19, 321 vs. $18, 833; P <0.001). Patients with decompensated cirrhosis (vs. compensated cirrhosis) had significantly higher inpatient mortality rates (5.8% vs. 1.1%; P <0.001) with higher LOS and costs ( P <0.001). On multivariable analysis, cirrhosis was associated with an increased risk of mortality (odds ratio, 4.22; 95% confidence interval, 2.92-6.10). Hospital cirrhosis volume was inversely associated with mortality, while hospital orthopedic procedure volumes had an inconsistent impact on outcomes. Conclusions: Inpatient orthopedic procedures in patients with cirrhosis result in high postoperative mortality, LOS, and costs. Careful patient selection is warranted to optimize cirrhosis patient postoperative outcomes. Abstract : Supplemental Digital Content is available in the text.